The Effect of PCM Capsule Material on the Thermal Energy Storage System Performance. (21st January 2014) - Reddy, R. Meenakshi; Nallusamy, N.; Reddy, K. Hemachandra
Abstract : Phase change material (PCM) based thermal energy storage (TES) systems are gaining increasing importance in recent years in order to reduce the gap between energy supply and demand in solar thermal applications. The present work investigates the effect of PCM capsule material on the performance of TES system during charging and discharging processes. The TES unit contains paraffin as PCM filled in spherical capsules and is integrated with flat plate solar collector. Water is used as sensible heat material as well as heat transfer fluid (HTF). The PCM capsules are of 68 mm diameter and are made using three different materials, namely, (i) high density polyethylene (HDPE), (ii) aluminum (Al), and (iii) mild steel (MS). The experimental investigation showed that the charging and recovery of stored energy are less affected by the spherical capsules material. The variables, like charging time and discharging quantity, are varied around 5% for the different capsule materials. Even though aluminum thermal conductivity is much higher than HDPE and mild steel, its influence on the performance of TES system is very low due to the very high internal heat resistance of PCM material stored in the spherical capsules.